Handbook for practical use of Exegetical Tools ways to help us get deeper meaning from the text - Grant-Henderson, Anna L. (Adelaide, SA MediaCom, 2007)
Includes bibliographical references.
Keywords: Bible -- criticsm, interpretation, etc